Una historia relacional: masones, redes y sociabilidad entre Canarias y América - Valeria Aguiar Bobet (Recherches, 2021)
Freemasonry has been studied in recent years as one of the first globalizing institutions in History, as one of the associations with the greatest diffusion of ideas, sociability practices and the transfer of people throughout the planet. The network of Masonic relationships, configured by a significant group of individuals in the Canary Islands from the mid-19th century to the 1930s, is immersed in this same framework. Our interest is in building a relational history from these networks and from the individuals who started them, consolidated them and revealed how they connected with each other.